179k views
17 votes
If 6(2b-4) = 0, then b=?

User Tamiz
by
5.8k points

2 Answers

9 votes

Answer:

b=2

Explanation:

We fist of all open the brackets.

6(2b-4) =0

= 12b-24=0

Then we combine like terms

( whenever a sign crosses over an equal to sign it changes)

12b = 0+24

12b=24

Divide by co-efficient of b which is 12

12b = 24

12 12

b=2

User Ameya Rote
by
5.8k points
14 votes

Answer:


  • \sf b=2

Explanation:


\sf 6(2b-4)=0

Divide both sides by 6.

(Anything divide by zero will give you zero, and anything plus zero gives itself)


\sf 2b - 4=0

Add 4 to both sides.


\sf 2b = 4

Divide both sides by 2.


\sf \cfrac{2b}{2}=\cfrac{4}{2}


\sf b = 2

_____________________

User Scottysseus
by
6.3k points